2008
DOI: 10.1186/1472-6955-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Dignity in the care of older people – a review of the theoretical and empirical literature

Abstract: Background: Dignity has become a central concern in UK health policy in relation to older and vulnerable people. The empirical and theoretical literature relating to dignity is extensive and as likely to confound and confuse as to clarify the meaning of dignity for nurses in practice. The aim of this paper is critically to examine the literature and to address the following questions: What does dignity mean? What promotes and diminishes dignity? And how might dignity be operationalised in the care of older peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
226
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(236 citation statements)
references
References 26 publications
4
226
0
6
Order By: Relevance
“…The term dignity comes from the Latin dignitas, and it seems generally accepted that the concept is related to an individual's characteristics, an intrinsic value, and an intersubjective value associated with being human (Gallagher et al 2008). Theoretical dignity has two distinct kinds of meaning: human dignity (Menschenwürde) and social dignity (Jacobson 2007, Nordenfelt andEdgar 2005).…”
Section: The Meaning Of Dignitymentioning
confidence: 99%
See 2 more Smart Citations
“…The term dignity comes from the Latin dignitas, and it seems generally accepted that the concept is related to an individual's characteristics, an intrinsic value, and an intersubjective value associated with being human (Gallagher et al 2008). Theoretical dignity has two distinct kinds of meaning: human dignity (Menschenwürde) and social dignity (Jacobson 2007, Nordenfelt andEdgar 2005).…”
Section: The Meaning Of Dignitymentioning
confidence: 99%
“…Caring might focus not only on the relationship between the nurse and the resident, but also on a network of relationships and a shared understanding of the daily life in the nursing home. Finally, it is important that care focuses on environmental and contextual values and conditions where the older persons´ interests and capabilities can flourish (Gallagher et al 2008, Rehnsfeldt et al 2014.…”
Section: Implications For Care In Nursing Homesmentioning
confidence: 99%
See 1 more Smart Citation
“…A UK study of over 2000 nurses (52) and a UK literature review (53) identified three broad areas that have the potential to enhance or diminish patient dignity in care. These are: staff attitudes and behaviour; the physical care environment; and organisational culture.…”
Section: Dignity and Nursing Ethics Researchmentioning
confidence: 99%
“…However, a review of the theoretical and empirical literature highlighted difficulties in defining dignity. 3 Of the literature reviewed on the subject, eight authors agree that it is easier to describe undignified care. [3][4][5][6][7][8][9][10] There have also been suggestions that dignity is a vague and nebulous concept detached from the reality of care delivery.…”
Section: Introductionmentioning
confidence: 99%